Iron Oxide Nanoparticle-Mediated mRNA Delivery to Hard-to-Transfect Cancer Cells - Jianxi Huang; Guanyou Lin; Taylor Juenke; Seokhwan Chung; Nicholas Lai; Tianxin Zhang; Tianyi Zhang; Miqin Zhang (MDPI AG, 2023)
mRNA-based therapeutics have emerged as a promising strategy for cancer treatment. However, the effective delivery of mRNA into hard-to-transfect cancer cells remains a significant challenge. This study introduces a novel approach that utilizes iron oxide nanoparticles (NPs) synthesized through a layer-by-layer (LbL) method for safe and efficient mRNA delivery. The developed NPs consist of an iron oxide core modified with a thin charge-bearing layer, an mRNA middle layer, and an outer layer composed of perfluorinated polyethyleneimine with heparin (PPH), which facilitates efficient mRNA delivery. Through a comparative analysis of four nanoparticle delivery formulations, we investigated the effects of the iron oxide core's surface chemistry and surface charge on mRNA complexation, cellular uptake, and mRNA release. We identified an optimal and effective mRNA delivery platform, namely, (IOCCP)-mRNA-PPH, capable of transporting mRNA into various hard-to-transfect cancer cell lines in vitro. The (IOCCP)-mRNA-PPH formulation demonstrated significant enhancements in cellular internalization of mRNA, facilitated endosomal escape, enabled easy mRNA release, and exhibited minimal cytotoxicity. These findings suggest that (IOCCP)-mRNA-PPH holds great promise as a solution for mRNA therapy against hard-to-transfect cancers.